2022
DOI: 10.14740/cr1392
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine Overdose in a Newborn: Precautions of Dispensing in Infants

Abstract: Ivabradine is currently approved to reduce heart rate in children with chronic heart failure and dilated cardiomyopathy. Ivabradine has also been used off-label in children to treat automatic tachyarrhythmias such as ectopic atrial tachycardia and junctional ectopic tachycardia. Adverse effects of ivabradine at physiological doses as well as its toxicity at supra-physiological doses have rarely been reported in adults. In children, weight-based dosing requires dilution of commercially available ivabradine oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…In our case, return to normal sinus rhythm was observed 1 h after the first dose of ivabradine. It has been previously reported that it takes 1 h for ivabradine to reach its peak plasma concentration after oral/internal use 9 . Ivabradine‐related side effects were not observed in our case.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…In our case, return to normal sinus rhythm was observed 1 h after the first dose of ivabradine. It has been previously reported that it takes 1 h for ivabradine to reach its peak plasma concentration after oral/internal use 9 . Ivabradine‐related side effects were not observed in our case.…”
Section: Discussionsupporting
confidence: 47%
“…It has been previously reported that it takes 1 h for ivabradine to reach its peak plasma concentration after oral/internal use. 9 Ivabradine-related side effects were not observed in our case. Similar to the literature, ivabradine 0.05 mg/kg/dose was effective and safe in our patient.…”
Section: Discussionsupporting
confidence: 37%
“…Ivabradine primarily acts on the If channels of cardiac cells, modulating cardiac electrophysiological activity. The incidence of common adverse reactions is mainly concentrated in the cardiovascular system, especially affecting cardiac electrophysiology and the conduction system, including bradycardia, increased heart rate, and atrial brillation (AF) [6, [19][20][21]. Although the expected side effect of ivabradine is sinus bradycardia, the side effect of causing tachycardia seems contradictory to its mechanism of action.…”
Section: Discussionmentioning
confidence: 99%